2022
DOI: 10.1111/acel.13698
|View full text |Cite
|
Sign up to set email alerts
|

Comet assay for quantification of the increased DNA damage burden in primary human chondrocytes with aging and osteoarthritis

Abstract: It is known that chondrocytes from joints with osteoarthritis (OA) exhibit high levels of DNA damage, but the degree to which chondrocytes accumulate DNA damage during “normal aging” has not been established. The goal of this study was to quantify the DNA damage present in chondrocytes obtained from cadaveric donors of a wide age range, and to compare the extent of this damage to OA chondrocytes. The alkaline comet assay was used to measure the DNA damage in normal cartilage from the ankle (talus) and the knee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 36 publications
2
28
0
Order By: Relevance
“…We also demonstrated that the TT-comet assay could detect DSB and SSB formation separately in non-sperm cells. Recently, Copp et al, assessed DNA strand breaks in chondrocytes from cadaveric doners using the TT-comet assay [ 27 ]. Therefore, this assay may be applicable for the detection of both types of strand breaks in other cell types and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated that the TT-comet assay could detect DSB and SSB formation separately in non-sperm cells. Recently, Copp et al, assessed DNA strand breaks in chondrocytes from cadaveric doners using the TT-comet assay [ 27 ]. Therefore, this assay may be applicable for the detection of both types of strand breaks in other cell types and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the DNA repair signaling pathway is crucial for the maintenance of chondrocyte homeostasis and anti-senescence, especially during aging ( 51 ). Previous studies have shown that TSPYL2 plays an important role in DNA damage repair and revealed the molecular mechanisms whereby TSPYL2 regulates SIRT1 and p53 activity upon DNA damage ( 35 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Age-related diseases of the musculoskeletal system are important determinants of quality of life in old age. Our current understanding is that cell autonomus and nonautonomus pathways interact to regulate aging processes in the bone, joints and skeletal muscle, which are also modulated by lifestyle factors (108)(109)(110)(111)(112). PACAP had a positive effect on chondrogenesis and bone formation in both in vivo and in vitro studies.…”
Section: Diseases Of the Musculoskeletal Systemmentioning
confidence: 99%